A = (M = a > b) & (n = C > d) | + + a = = B --; what is the operation process of this expression, a=(m=a>b)&&(n=c>d)||++a==b-- After reading the book, I found that (M = a > b) & (n = C > d) and + + a = = B -- last a= Give it to you. It's a waste if you don't give it, hehe

A = (M = a > b) & (n = C > d) | + + a = = B --; what is the operation process of this expression, a=(m=a>b)&&(n=c>d)||++a==b-- After reading the book, I found that (M = a > b) & (n = C > d) and + + a = = B -- last a= Give it to you. It's a waste if you don't give it, hehe


( a=( ((m=(a>b))&&(n=(c>d))) || (++a) ) )==(b--)
Operate in my bracketed order
The problem of operator priority is explained in detail in all C language textbooks
Real programs don't write like this either, because there's an easy way: when you're too lazy to figure out the priority, just add parentheses (the highest priority) to the part you want to calculate first



Int a = 3; after finding the value of the expression a = ('m '>'n')? A + 2: A-2, a + 3,3 * a, the value of a is the calculation order


a = ('m' >'n')?a+2:a-2,a+3,3*a
Equivalent to a = true? A + 2: A-2;
It is equivalent to a = a + 2; a = 5;
The order of operations is from left to right
A + 3,3 * a has no meaning here



0.5y-0.3x of x-0.2y A-1 / 2 of 3 / 4-b does not change the value of the fraction. Change the coefficients of the following numerator and denominator into integers


Solution 0.5y-0.3x x-0.2y
=10x-2y of 5y-3x
A-1 / 2 / 3 / 4-b.. (numerator denominator at the same time × 4)
=4a-3 / 2-4b



Take off the formula to calculate. (can calculate simple to calculate) quickly, quickly
(7 / 8 + 3 / 16) * (5 / 9 + 1 / 3)
(1 / 3 + 11 / 12-3 / 4) / 1 / 24
5 / 4 / 6-2 / 9 * 3 / 4
1 / {(3 / 4 + 1 / 3) / 5 / 8}


7 / 8 + 3 / 16) * (5 / 9 + 1 / 3)
=(14/16+3/16)*(5/9+3/9)
=17/16*8/9
=17/18
(1 / 3 + 11 / 12-3 / 4) / 1 / 24
=1/3*24+11/12*24-3/4*24
=8+22-18
=12
5 / 4 / 6-2 / 9 * 3 / 4
=5/6*4/3-2/9*3/4
=3/4*(15/18-4/18)
=3/4*11/18
=11/24
1 / {(3 / 4 + 1 / 3) / 5 / 8}
=1/(13/12*8/5)
=1/26/15
=15/26



1. If | a | = - A, then the rational number a is () A. positive number B. negative number C. positive number and zero D. negative number sum
1. If | a | = - A, then the rational number a is () A. positive number B. negative number C. positive number and zero D. negative number and zero 2________ (have)a music lesson on Monday.


1, D 2



Given that K is the root of the equation x ^ 2-3x + 1 = 0, find the value of 2K ^ 2-5k-2 + 3 / K ^ 2 + 1


We can get: K & # 178; - 3K + 1 = 0, that is: K & # 178; + 1 = 3K
Divide both sides by K to get K + 1 / k = 3
(2k²-5k-2)+3/(k²+1)
=[2(k²+1)-2-5k-2)+3/3k
=[6k-5k-4]+1/k
=k+1/k-4
=3-4
=-1



1. A car can travel 5 / 8 kilometers in 3 / 4 minutes. How many kilometers can the car travel in 1 minute? Half an hour?
2. A feed grinder can crush 1 / 8 ton of feed in 1 / 4 hour. How many tons of feed can this feed grinder crush in 1 hour?
3. 800 kg of refined salt needs to be packed in bags. If each small bag contains 1 / 4 kg, how many small bags do you need?


A car can travel 5 / 8 kilometers in 3 / 4 minutes. How many kilometers can the car travel in 1 minute? Half an hour?
One minute: 5 / 8 * 4 / 3 = 5 / 6 (km)
Half hour: 5 / 6 * 30 = 25 (km)
A feed grinder can crush 1 / 8 ton of feed in 1 / 4 hour. How many tons of feed can this feed grinder crush in 1 hour?
1 / 8 * 4 = 1 / 2 (ton)
800 kg of refined salt needs to be packed in bags. If each small bag contains 1 / 4 kg, how many small bags do you need?
800 * 4 = 3200



What is LIM (x → 0) e ^ 2x - 1
The note is 2x / x = 2, I suspect it is wrong
According to the equivalent infinitesimal
Isn't it equivalent to 2x?


If X - > 0, e ^ 2x = e ^ 0 = 1,1-1 = 0



What is the greatest common factor of polynomials x ^ 4 + 2x ^ 3-4x ^ 2-2x + 3 and x ^ 3 + 4x ^ 2 + X-6


x^4+2x^3-4x^2-2x+3=(x^4+3x^3)-x(x^2+4x+3)+(x+3)=x^3(x+3)-x(x+1)(x+3)+(x+3)=(x+3)[x^3-x(x+1)+1]=(x+3)[x^3+1-x(x+1)]=(x+3)[(x+1)(x^2-x+1)-x(x+1)]=(x+3)(x+1)(x^2-2x+1)...



Minus 5 times 7 / 25 plus minus 7 times 7 / 25 minus 12 times 7 / 25 is calculated by multiplication law


Minus 5 times 7:25 plus minus 7 times 7:25 minus 12 times 7:25
=(-5-7+12)×25/7
=0×25/7
=0